Hydrogels in Spinal Cord Injury Repair: A Review - Lv, Zhenshan; Dong, Chao; Zhang, Tianjiao; Zhang, Shaokun (Frontiers in Bioengineering and Biotechnology, 2022)
Traffic accidents and falling objects are responsible for most spinal cord injuries (SCIs). SCI is characterized by high disability and tends to occur among the young, seriously affecting patients’ lives and quality of life. The key aims of repairing SCI include preventing secondary nerve injury, inhibiting glial scarring and inflammatory response, and promoting nerve regeneration. Hydrogels have good biocompatibility and degradability, low immunogenicity, and easy-to-adjust mechanical properties. While providing structural scaffolds for tissues, hydrogels can also be used as slow-release carriers in neural tissue engineering to promote cell proliferation, migration, and differentiation, as well as accelerate the repair of damaged tissue. This review discusses the characteristics of hydrogels and their advantages as delivery vehicles, as well as expounds on the progress made in hydrogel therapy (alone or combined with cells and molecules) to repair SCI. In addition, we discuss the prospects of hydrogels in clinical research and provide new ideas for the treatment of SCI.